'A model co-operative country': Irish–Finnish contacts at the turn of the twentieth century. Issue 160 (8th November 2017) - Hilson, Mary
Abstract: Agricultural co-operative societies were widely discussed across late nineteenth-century Europe as a potential solution to the problems of agricultural depression, land reform and rural poverty. In Finland, the agronomist Hannes Gebhard drew inspiration from examples across Europe in founding the Pellervo Society, to promote rural cooperation, in 1899. He noted that Ireland's 'tragic history', its struggle for national self-determination and the introduction of co-operative dairies to tackle rural poverty, seemed to offer a useful example for Finnish reformers. This article explores the exchanges between Irish and Finnish co-operators around the turn of the century, and examines the ways in which the parallels between the two countries were constructed and presented by those involved in these exchanges. I will also consider the reasons for the divergence in the development of cooperation, so that even before the First World War it was Finland, not Ireland, that had begun to be regarded as 'a model co-operative country'.